2021
DOI: 10.1007/s00418-021-02014-8
|View full text |Cite
|
Sign up to set email alerts
|

Role of ascorbic acid in the regulation of epigenetic processes induced by Porphyromonas gingivalis in endothelial-committed oral stem cells

Abstract: Periodontitis is a common inflammatory disease that affects the teeth-supporting tissue and causes bone and tooth loss. Moreover, in a worldwide population, periodontal disease is often associated with cardiovascular diseases. Emerging studies have reported that one of the major pathogens related to periodontitis is Porphyromonas gingivalis (P. gingivalis), which triggers the inflammatory intracellular cascade. Here, we hypothesized a possible protective effect of ascorbic acid (AA) in the restoration of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 53 publications
(51 reference statements)
1
4
0
Order By: Relevance
“…In the present study, P. gingivalis LPS attenuated the gene expression of DNMTs , enzymes facilitating and maintaining the DNA methylation. The modulation of DNMTs corroborates with the previous findings [ 29 , 31 ]. The decreased expression of DNMTs may lead a hypomethylation pattern in P. gingivalis LPS-treated cells, while hypomethylation of the genes is closely linked to transcriptional upregulation [ 49 ], indicating that DNMTs might be involved in the cytokine upregulations in P. gingivalis LPS-treated cells.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In the present study, P. gingivalis LPS attenuated the gene expression of DNMTs , enzymes facilitating and maintaining the DNA methylation. The modulation of DNMTs corroborates with the previous findings [ 29 , 31 ]. The decreased expression of DNMTs may lead a hypomethylation pattern in P. gingivalis LPS-treated cells, while hypomethylation of the genes is closely linked to transcriptional upregulation [ 49 ], indicating that DNMTs might be involved in the cytokine upregulations in P. gingivalis LPS-treated cells.…”
Section: Discussionsupporting
confidence: 92%
“…Epigenetic modulations are regarded as a profoundly supplementary mechanisms determining the way in which chronic inflammatory diseases affect multiple systemic disorders [ 28 ]. Previous studies showed that P. gingivalis LPS could alter the gene expression of the DNA methyltransferase family (DNMTs) and ten-eleven translocation proteins (TETs) in vitro [ 29 , 30 , 31 ]. Here, we investigated the mRNA expression levels of the two common epigenetic enzymes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mesenchymal stem cells (MSCs) are stromal cells characterized by the ability to undergo self-renewal, guaranteeing a pool of stem cells, and to differentiate into mesodermal, ectodermal and endodermal cell lineages. The latter enables them to subsequently differentiate into osteoblasts, adipocytes, chondrocytes (mesodermal lineage), neurons (ectodermal lineage) and liver cells (endodermal lineage) under specific in vitro conditions (Pizzicannella et al 2021b ). MSCs express cluster of differentiation (CD) surface markers that allow them to be characterized and distinguish them from the hematopoietic cells, especially by evaluating the lack of the expression of CD14, CD34, CD45 and human leukocyte antigen (HLA-DR) and positivity for CD73, CD90, nestin and βIII tubulin (Tuj-1) as neuronal markers, CD146 and CD105 asendothelial markers, transforming growth factor beta (TGF β) receptor and several integrins (Soundara Rajan et al 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…When exposed to AA, the physiological ROS levels were restored. [ 25 ] Ascorbic acid had shown to have positive effects on gingival fibroblast by different mechanisms and pathways. Our team has extensive knowledge and research experience that has translate into high quality publications.…”
Section: Discussionmentioning
confidence: 99%